2020
DOI: 10.3390/app10196786
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Decision-Making in Collaborative Cognitive Radio Networks

Abstract: Spectral decision making is a function of the cognitive cycle. It aims to select spectral opportunities within a set of finite possibilities. Decision-making methodologies, based on collaborative information exchanges, are used to improve the selection process. For collaborative decision making to be efficient, decisions need to be analyzed based on the amount of information. Using little data can produce inefficient decisions, and taking a lot of data can result in high computational costs and delays. This do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Hence, using this categorization, it is possible to choose a suitable spectrum band. The investigator of the current study explores the channel properties, decision processes, and research issues in CRN as per the following [9].…”
Section: Figure 1: Radio Environmentmentioning
confidence: 99%
“…Hence, using this categorization, it is possible to choose a suitable spectrum band. The investigator of the current study explores the channel properties, decision processes, and research issues in CRN as per the following [9].…”
Section: Figure 1: Radio Environmentmentioning
confidence: 99%
“…The second module allows including collaborative decision-making processes through the exchange of information between SU. In (Giral et al, 2020) the structure of the developed collaborative module is described in detail. This module, as shown in Figure 1, is connected to the Spectral Information Module.…”
Section: Collaborative Modulementioning
confidence: 99%
“…For this research, the assigned environments are according to the level of collaboration that presents the most efficient results. This level can be parameterized between 10 % and 100 % (Giral et al, 2020) address this feature in their work, where the authors showed that the range for the collaboration level with the best results is between 20 % and 50 %. As an additional element, this paper analyzed a level of collaboration outside this range.…”
Section: Collaborative Modulementioning
confidence: 99%
“…Lo anterior se logra a partir de un modelo de gestión denominado ciclo cognitivo, el cual es una estructura de radio que puede reconfigurarse mediante un proceso continuo de conciencia (tanto de sí mismo como del mundo exterior), percepción, razonamiento y toma de decisiones (Haykin, 2005). El ciclo cognitivo se caracteriza por cuatro funciones principales: detección del espectro, decisión de espectro, movilidad espectral y compartición de espectro (Giral et al, 2020;Hernandez et al, 2020;Hernandez et al, 2020a).…”
Section: Introductionunclassified